The Impact of Loading Dose on Outcome in Stroke Patients Receiving Low-Dose Tissue Plasminogen Activator Thrombolytic Therapy - Wong YS; Sung SF; Wu CS; Hsu YC; Su YH; Hung LC; Ong CT (Dove Medical Press, 2020)
Yi-Sin Wong, 1 Sheng-Feng Sung, 2 Chi-Shun Wu, 2 Yung-Chu Hsu, 2 Yu-Hsiang Su, 2 Ling-Chien Hung, 2 Cheung-Ter Ong 2 1Department of Family Medicine, Chia-Yi Christian Hospital, Chia-Yi, Taiwan; 2Department of Neurology, Chia-Yi Christian Hospital, Chia-Yi, TaiwanCorrespondence: Cheung-Ter OngDepartment of Neurology, Chia-Yi Christian Hospital, 539 Chung-Shao Road, Chia-Yi, TaiwanTel +886-5-2765041Email ctong98@yahoo.com.twBackground: Intravenous tissue plasminogen activator (tPA) (0.9 mg/kg, maximum 90 mg) with a bolus of 10% of the total dose given within 1– 2 mins is the standard therapy for patients receiving thrombolytic therapy. Low-dose (0.6 mg/kg) tPA is also approved for thrombolytic therapy for ischemic stroke patients. Low-dose tPA is associated with a low bolus dose. It is unknown whether increasing the bolus dose in patients receiving low-dose tPA thrombolysis may improve outcomes or increase the risk of hemorrhagic transformation (HT).Aim: This study investigated the impact of the bolus dose on the outcome in ischemic stroke patients receiving low-dose tPA thrombolytic therapy.Methods: In this retrospective, observational study, we enrolled 214 ischemic stroke patients receiving low-dose tPA thrombolytic therapy. Of these 214 patients, 107 patients received 10% of the total dose as a bolus dose, and 107 patients received 15% of the total dose as a bolus dose. The National Institutes of Health Stroke Score (NIHSS) were evaluated before tPA infusion, 24 h after thrombolytic therapy, and at discharge. Stroke severity was categorized as mild (0– 5), moderate (6– 14), severe (15– 24), or very severe (≥ 25). Neurological improvement (NI) was defined as an improvement of 6 or more points in the NIHSS, and no response (NR) was defined as an increase in the NIHSS of ≤ 4 points or a decrease ≤ 6 points. Neurological deterioration (ND) was defined as an increase in the NIHSS > 4 points. A good outcome was defined as a modified Ranking Score (mRS) of 0 or 1. We compared the NI, NR, and ND rates at 24 hrs after thrombolytic therapy and discharge between the 15% and 10% bolus dose groups.Results: In patients with mild and moderate stroke, there was no significant difference in the NI, NR, ND, and HT rates and 6-month outcomes between the 15% and 10% bolus groups. In patients with severe and very severe stroke, outcomes at 6 months were significantly better in the 15% bolus group than in the 10% bolus group. The factors affecting the outcomes of severe and very severe stroke patients are hypertension and bolus dose.Conclusion: In severe and very severe stroke patients receiving low-dose tPA thrombolytic therapy, a bolus dose of 15% of the total dose can improve outcomes.Keywords: ischemic stroke, tPA, thrombolysis, hypertension, outcome